Humanoid Robot Path Planning Using Rapidly Explored Random Tree and Motion Primitives - Szumowski, Maksymilian; Zielińska, Teresa (Journal of Automation, Mobile Robotics and Intelligent Systems, 2024)
Path planning is an essential part of the control system of any mobile robot. In this article the path planner for a humanoid robot is presented. The short description of an universal control framework and the Motion Generation System is also presented. Described path planner utilizes a limited number of motions called the Motion Primitives. They are generated by Motion Generation System. Four different algorithms, namely the: Informed RRT, Informed RRT with random bias, and RRT with A* like heuristics were tested. For the last one the version with biased random function was also considered. All mentioned algorithms were evaluated considering three dif ferent scenarios. Obtained results are described and discussed.